Teaching Time Investment: Does Online Really Take More Time than Face-to-Face? - Van de Vord, Rebecca; Pogue, Korolyn (International Review of Research in Open and Distributed Learning, 2012)
Enrollments in online programs are growing, increasing demand for online courses. The perception that teaching online takes more time than teaching face-to-face creates concerns related to faculty workload. To date, the research on teaching time does not provide a clear answer as to the accuracy of this perception. This study was designed to investigate which aspects, if any, are more time consuming for instructors teaching in the online environment. Time logs were kept by four online instructors (eight classes) and six on-campus instructors (six classes) through six weeks of the 15-week semester. Results indicated that, overall, face-to-face teaching required more time per student, but certain aspects of online teaching take considerably more time per student than in the face-to-face classroom.